O swing da cor : a linguagem política do orgulho negro na black music brasileira (1960-88) - Bruno Vinicius Leite de Morais (2022)
This dissertation approaches the production of Brazilian Black Music released between 1960 and 1988, analyzing the circulation of anti-racist political ideas in the songs. The research identified the affirmation of black culture and the denunciation of racial prejudice in Brazil as frequent themes in a Brazilian musical production that hybridized or incorporated sounds from American Black Music. The initial mark of such production was located in 1960, with the first LP by Elza Soares and the emergence of Bossa Negra, also developed by Jorge Ben and Wilson Simonal. Starting with Bossa Negra, the research identified, in the late 1960s, the incorporation of Soul and Funk, which became hegemonic in Brazilian Black Music and reached their prime in the 1970s, with several artists. Along with the sounds, the research also identified in the lyrics of the songs, from 1967 onwards, a movement of dialogue with the reality of American black communities, in what was called the Political Language of Black Pride. In the final mark, the 1980s, the research found the withdrawal of Black Music Brasileira sounds in the phonographic market. Among the conclusions of the research on the dissemination of the anti-racist theme, there was the location of an effort by the anti-racist black militancy to change the understanding of the word “racism”: from asserting the superiority of a race and segregationism to prejudice and discrimination against black communities, an understanding that would have contributed to the deconstruction of the ideals of “racial democracy” in Brazil as a myth.